With a little profitable help from my friends: the relational incongruence of benefiting financially from prosocially motivated favors - Arnestad, Mads Nordmo; Glambek, Mats; Selart, Marcus (Frontiers in Behavioral Economics, 2024)
To improve our understanding of how people engage in altruistic behavior, it is important to investigate the motives provided by help recipients and how these motives influence givers’ helping behavior. In the present study, we explore how the financial motivation of help recipients can affect givers’ helping behavior. Across three experiments (total N=606), we find that people like to help others, but resent helping those motivated by immediate financial gains. Study 1 shows that the recipient of help influenced the responses of the helpers depending on if the recipient was making a sales profit from this help or not. An influencing factor was whether the recipient could provide an excuse for making such a profit. Study 2 replicated these findings also in conditions where other kinds of profits were applied. Study 3 confirmed the results in conditions where helpers were informed about recipients’ financial motives prior to deciding on helping or not.